2003
DOI: 10.1111/1467-9671.00159
|View full text |Cite
|
Sign up to set email alerts
|

Using the Relative Operating Characteristic to Quantify Certainty in Prediction of Location of Land Cover Change in India

Abstract: This paper describes a methodology by which modelers, ecologists and planners can quantify the certainty in predicting the location of change for a given quantity of change. The specification of the quantity of a land cover category and the specification of the location of a land cover category are two distinct fundamental concepts in geographical analysis. It is crucial that scientists have appropriate quantitative tools to analyze each of these two concepts independently of one another. This paper gives meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 10 publications
1
45
0
Order By: Relevance
“…ROC curve statistic can examine the accuracy of prediction at several different threshold levels, then aggregate the information at all thresholds into one measure of agreement [26]. So, this method can give overall assessment for prediction ability of a stochastic probability model, for example, SLEUTH.…”
Section: The Effectiveness Of the Multi-methods For Assessment Of Modmentioning
confidence: 99%
“…ROC curve statistic can examine the accuracy of prediction at several different threshold levels, then aggregate the information at all thresholds into one measure of agreement [26]. So, this method can give overall assessment for prediction ability of a stochastic probability model, for example, SLEUTH.…”
Section: The Effectiveness Of the Multi-methods For Assessment Of Modmentioning
confidence: 99%
“…Finally, the receiver operating characteristic (ROC) curve analysis is a quantitative measurement tool to validate the goodness of fit of an LUCC model [20,[76][77][78]. Sensitivity (true positive rate) and specificity (true negative rate) are calculated using the formula below, based on the overall agreement cell score outputs.…”
Section: Accuracy and Reliabilitymentioning
confidence: 99%
“…False positive rates and true positive rates are plotted along X and Y axes for each threshold. The area under the ROC curve represents the model accuracy [43]. The calculated PCM (90%) and ROC (85%) indicated that the accuracy of trained model was high enough to be used for future land cover prediction [30].…”
Section: Model Calibrationmentioning
confidence: 99%